Internal Disulfide Bonding and Glycosylation of Interleukin-7 Protect Against Proteolytic Inactivation by Neutrophil Metalloproteinases and Serine Proteases - Vandooren, Jennifer; Pereira, Rafaela Vaz Sousa; Ugarte-Berzal, Estefania; Rybakin, Vasily; Noppen, Sam; Stas, Melissa R.; Bernaerts, Eline; Ganseman, Eva; Metzemaekers, Mieke; Schols, Dominique; Proost, Paul; Opdenakker, Ghislain (Frontiers in Immunology, 2021)
Interleukin 7 (IL-7) is a cell growth factor with a central role in normal T cell development, survival and differentiation. The lack of IL-7–IL-7 receptor(R)-mediated signaling compromises lymphoid development, whereas increased signaling activity contributes to the development of chronic inflammation, cancer and autoimmunity. Gain-of-function alterations of the IL-7R and the signaling through Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) are enriched in T cell acute lymphoblastic leukemia (T-ALL) and autocrine production of IL-7 by T-ALL cells is involved in the phenotypes of leukemic initiation and oncogenic spreading. Several IL-7-associated pathologies are also characterized by increased presence of matrix metalloproteinase-9 (MMP-9), due to neutrophil degranulation and its regulated production by other cell types. Since proteases secreted by neutrophils are known to modulate the activity of many cytokines, we investigated the interactions between IL-7, MMP-9 and several other neutrophil-derived proteases. We demonstrated that MMP-9 efficiently cleaved human IL-7 in the exposed loop between the α-helices C and D and that this process is delayed by IL-7 N-linked glycosylation. Functionally, the proteolytic cleavage of IL-7 did not influence IL-7Rα binding and internalization nor the direct pro-proliferative effects of IL-7 on a T-ALL cell line (HPB-ALL) or in primary CD8+ human peripheral blood mononuclear cells. A comparable effect was observed for the neutrophil serine proteases neutrophil elastase, proteinase 3 and combinations of neutrophil proteases. Hence, glycosylation and disulfide bonding as two posttranslational modifications influence IL-7 bioavailability in the human species: glycosylation protects against proteolysis, whereas internal cysteine bridging under physiological redox state keeps the IL-7 conformations as active proteoforms. Finally, we showed that mouse IL-7 does not contain the protease-sensitive loop and, consequently, was not cleaved by MMP-9. With the latter finding we discovered differences in IL-7 biology between the human and mouse species.